The Effect of Endogenous Regulation on Telecommunications Expansion and Efficiency in Latin America (2003)
I examine the effect of reform on telecom performance using a second-generation regulatory framework index and panel data techniques to test how regulatory governance affected sector performance in 22 Latin American countries during the period 1980-1997. Sound regulatory governance in telecommunications has a positive impact on network expansion and efficiency, in both the static and dynamic specifications. Openness of markets to competition and divestment of former state-owned telco operators also contributed positively to better sector performance. The dynamic specification shows that past performance has its own strong effect on present (and perhaps future) performance.